90.0k views
1 vote
Can someone help me im kinda dumb :/

Can someone help me im kinda dumb :/-example-1

1 Answer

2 votes

Answer:

9. a₁ = 13, aₙ = aₙ₋₁ × (-2)

10. aₙ = 2 (-3)ⁿ⁻¹

Explanation:

9. aₙ = 13 (-2)ⁿ⁻¹

This is a geometric sequence where the first term is 13 and the common ratio is -2.

So the recursive formula is:

a₁ = 13, aₙ = aₙ₋₁ × (-2)

10. a₁ = 2, aₙ = aₙ₋₁ × (-3)

This is a geometric sequence where the first term is 2 and the common ratio is -3.

So the explicit formula is:

aₙ = 2 (-3)ⁿ⁻¹

User Paulooze
by
5.7k points